Developmental theism from pure will to unbounded love - Forrest, Peter, 1948- (Oxford : Clarendon, 2010)
This is a work of speculative theology based on three themes that a version of materialism is a help not a hindrance in philosophical theology; that God develops; and that this development is on the whole kenotic, in other words an abandonment of power.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophical theology